The dynamics between trade openness and innovation The case of the Uruguayan exporting company - Silveira, Luis; Albertoni, Nicolás (Estudios de Administración, 2023)
This document attempts to investigate whether the level of trade openness has an influence on the probability that Uruguayan manufacturing companies carry out innovation activities. It is shown that the level of commercial openness, considered this as the percentage of exports in the level of total sales, positively influenced the innovation activities carried out by the Uruguayan manufacturing companies, in particular the activities that had to do with R&D, both internal and external, intellectual property, engineering and design, marketing and brand management and management of the innovation itself. It also emerged from the research that the existence of formal R&D units and state support also positively influenced the probability that the companies were innovative.